O-007 Natural History of Acute Ischaemic Stroke from Large Vessel Occlusion Demonstrates Efficacy of Mechanical Thrombectomy: Preliminary Results of the Penumbra FIRST Study. (14th July 2013) - Janardhan, V; Carlson, L; Gianatasio, R; Chen, S; Bhuva, P; Murray, M; Vijayappa, M; Hansen, P; Cheung, R; Leung, T; Grunwald, I; Hernandez, H; et al.
Abstract : Introduction/Purpose: Current literature has only limited information on the natural history of the stroke cohort eligible for mechanical thrombectomy. This has contributed to the uncertainties over the benefits of mechanical thrombectomy devices since they were approved either by single arm trials or with another device as active control. The aim of FIRST is to gather real world control data to reference results from mechanical thrombectomy trials in the proper context. Materials and Methods: The FIRST Trial is a prospective, multicentre, single arm natural history study of a stroke cohort eligible for but untreated by endovascular therapy presenting within 8 hours of symptom onset from a large vessel occlusion and a NIHSS score ≥10. Patients should be ineligible or refractory to lytic therapy. The primary endpoint is 90-day functional outcome as defined by a mRS 0–2. Results: For this interim analysis, 61 enrolled patients met study criteria. The mean age was 67.7 ± 15.7 years; median NIHSS score was 18 (IQR14–22). Target vessel occlusions were located in the ICA (28%), MCA (67%), and other (5%). At admission, the TIMI 0–1 rate was 98% (59/60), and the TICI 0–1 rate was 98% (58/59). Of these, only 10% (4/41) and 12% (5/41) showed spontaneous recanalisation (TIMI 2–3 or TICI 2a-3). Twelve of 54 (22%) patients achieved a good 90-day outcome, and 25 of 61 (41%) died. The serious adverse event rate within 24 hours of stroke onset was 54% (33/61), including cerebral oedema (8 cases) and respiratory failure (4 cases). Eleven (18%) patients suffered intracerebral haemorrhage. 33 (56%) were refractory to IV rtPA. Compared with PROACT II placebo patients, the stroke cohort eligible for mechanical thrombectomy who were untreated have different baseline characteristics, a lower recanalisation rate, and worse outcome. The graph shows a comparison of 90-day good outcome in the FIRST vs Penumbra System Trials, trichotomised by pre-ASPECTS scores. Conclusion: Large vessel acute ischaemic stroke is a malignant disease wherein 78% of patients will either die or suffer long-term disabilities if untreated. When compared to the same stroke cohort without treatment, IA intervention with the Penumbra System consistently showed treatment effects. There are substantial differences in entry criteria and clinical outcomes between the FIRST and PROACT 2 patient populations. These results suggest it is not appropriate to use the PROACT placebo patients as historical controls for mechanical thrombectomy trials. FIRST data may serve as a benchmark for future trials. Disclosures: V. Janardhan: None. L. Carlson: None. R. Gianatasio: None. S. Chen: None. P. Bhuva: None. M. Murray: None. M. Vijayappa: None. P. Hansen: None. R. Cheung: None. T. Leung: None. I. Grunwald: 6; C; Penumbra, Inc. H. Hernandez: 5; C; Penumbra, Inc. L. Barraza: 5; C; Penumbra, Inc. H. Buell: 5; C; Penumbra, Inc. S. Kuo: 5; C; Penumbra, Inc. A. Bose: 4; C; Penumbra, Inc. 5; C; Penumbra, Inc. S. Sit: 4; C; Penumbra, Inc. 5; C; Penumbra, Inc.